(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This Research studied the T C Conharmonic curvature tensor of almost kahler-manifold, where this research focuses on the geometrical feature or properties of the one of the almost kahler-manifold.